ANISARA (Quantum Learning Speaking Arabic) as A Strategy to Improve Arabic Speaking Skills - Suyadi, Nurjanah Pujirahayu; Hidayati , Laily Nur; Bahraini, Laisa (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Quantum Learning Arabic is inspired by Quantum Teaching, a learning model developed by Bobby DePorter. Quantum Learning creates learning with a Quantum Teaching model that focuses on speaking or speaking Arabic skills. The ANISARA (Quantum Learning Speaking Arabic) strategy is a strategy that contains an Arabic language learning model that supports the improvement of Arabic skills. It strives to maximize all the skills and potential that students have and make the lessons carried out by educators to the maximum so that students themselves can also maximize the absorption of materials. The study aims to describe the model or statics of learning Arabic, especially speech skills using the Quantum learning model of Speaking Arabic. The research method used is research (research and development). R&D research is conducted with stages that consist of analysis, design, development, and implementation.